COMBINATORIAL PROPERTIES OF THE DIFFERENCE SET WITH RESPECT TO CPHMs OF ROW SUM 0 AND 2 - Manjhi, Pankaj Kumar; Kumar, Jitendra (Communications in Mathematics and Applications, 2025)
This article investigates the combinatorial properties of difference sets within the cyclic group Zn, specifically in the context of circulant partial Hadamard matrices (CPHMs). We examine the structural characteristics and establish relationships between difference sets associated with 2-H(m×n) and 0-H(m×n) matrices. Our results provide insights into the interplay between these matrix classes and their corresponding difference sets, contributing to the broader understanding of their applications in combinatorial design theory.